Beban Pendingin Plug-in Cold Room GEA Tipe (GAC-245) untuk Pengawetan Ikan - Suyanto, Suyanto (Marine Science and Technology Journal, 2022)
One way of handling caught fish so that freshness is maintained is by lowering the temperature or cooling the temperature of the fish. At low temperatures, the biochemical processes that take place in the fish's body that lead to a decrease in fish quality take place more slowly. In addition, at low temperature conditions the growth of spoilage bacteria in the fish's body can also be slowed down. This study aims to calculate the cooling load on the use of cold room GEA type GAC-245 for fish preservation. With the resulting total cooling load and the percentage of cooling load can be considered in the use of the cold room. The results showed that the total cooling load was 9460 Watt. The biggest cooling load is the product load with a value of 6475 Watt. The infiltration load is quite large in the second order, so to reduce the use of cold storage, efforts are made so that the door does not open too long or too often.